Isolation and characterization of chalcone synthase (CHS) gene from Phalaenopsis and Doritaenopsis orchids - Dewi Sukma; Aline Sisi Handini; Sudarsono Sudarsono (Society for Indonesian Biodiversity, 2020)
Abstract. Sukma D, Handini AS, Sudarsono. 2020. Isolation and characterization of chalcone synthase (CHS) gene from Phalaenopsis and Doritaenopsis orchids. Biodiversitas 21: 5054-5064. Chalcone synthase (CHS) is a key enzyme in flavonoid biosynthesis. The research aims to isolate and characterize the CHS gene nucleotide sequence diversity of nine Phalaenopsis and one Doritaenopsis genotypes. Genomic DNA was isolated from young leaves and used to PCR amplify the gene using CHS specific degenerate primers. Results of PCR amplification yielded DNA fragments of 700 bp. Upon sequencing and nucleotide sequence analysis, we found that the genomic fragments were partial CHS gene from Phalaenopsis and Doritaenopsis genotypes and deposited the sequences in the NCBI Genebank Database accession numbers of KR184089-KR184098. More analysis of the sequences confirmed they shared ranged from 81-99% sequence identities to known CHS genes from Phalaenopsis deposited in the NCBI Database. They also shared 84-100% amino acid residues identity to CHS polypeptides. Multiple sequence alignment (MSA) and phylogenetic analysis further revealed the determined CHS nucleotide sequences from Phalaenopsis and Doritaenopsis genotypes were closely related to CHS genes from other orchid species.